Digitalisasi Laporan Keuangan Bagi UMKM - Nabila Amalia Nurrohmah; Deri Darmawan; Rudi Sanjaya (International Forum of Researchers and Lecturers, 2024)
The digitalization era has contributed significantly to the progress and convenience of human life, especially in accessing information quickly and openly. In this context, digitalization also improves the management of financial reports for MSMEs, making them more effective and efficient. This study aims to examine the role of digitalization in MSME financial reporting activities and the challenges faced in implementing digital financial reports. Using a literature review approach, this study focuses on collecting relevant data and insights to analyze the impact of the digital financial reporting system. The results show that digitalization minimizes errors in financial reports and opens up wider funding opportunities for MSMEs, thereby improving their financial management and overall competitiveness.